Pilmapres 2026 of State Polytechnic of Sriwijaya: Mentoring Outstanding Students in Strengthening Portfolio, Innovative Products, and English Proficiency - Rahman, M Arief; Paisal; Wahyu Triaji Rahadianto; Melisa Kurnia Asfitri; Indah Pratiwi; Dicky Seprianto (STIKES Columbia Asia Medan, 2026)
This community service activity aimed to strengthen the readiness of outstanding students of State Polytechnic of Sriwijaya in the Pilmapres 2026 selection through structured mentoring on achievement portfolio, innovative product, and English presentation. The program was designed as a participatory capacity-building activity involving needs identification, portfolio clinic, innovative product mentoring, English communication practice, presentation simulation, and reflective evaluation. The activity was implemented through technical meetings, document review, discussion, presentation practice, and feedback sessions involving students, supervisors, and institutional stakeholders. The results indicate that the mentoring process helped students organize evidence of achievement, sharpen the problem-solution logic of their innovative products, improve presentation confidence, and understand the assessment orientation of Pilmapres. Documentation of the activity shows the stages of preparation, selection, product presentation, and award ceremony. The program implies that continuous institutional mentoring is essential to build an ecosystem of student achievement, innovation, and English communication competence in vocational higher education.Keywords: Pilmapres; outstanding student; portfolio; innovative product; English presentation